A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMAN 1 KUBU IN READING COMPREHENSION - Al Rahmat Putra Al Rahmat Putra; Syofia Delfi Syofia Delfi; Fakhri Ras Fakhri Ras (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The purpose of this study is to find out the ability of the second year students of SMAN 1 Kubu in reading comprehension. This research focuses on students’ reading comprehension in terms of finding main ideas, factual information, the meaning of vocabulary, identifying references and making inferences,.The data were collected using reading comprehension test with multiple choice type. The test contained 25 items. The try out was conducted to check the validity and reliability of the test. Based on the research, it was found out that first: the ability of the second year students in reading comprehension is in the mediocre level with the mean score of 54.9. Second, the students’ mean score in finding the main idea is in good level with the mean score of 61.47, finding the factual information is in mediocre level with the mean score of 51.76, in finding the meaning of vocabulary is in good level with the mean score of 61.17, in finding references is in mediocre level with the mean score of 53.5, in finding inference is in mediocre level with the mean score of 46.47. As a conclusion, the highest score obtained by the students is in finding main ideas with the mean score of 61,47 which is categorized.into good level , and the lowest score that the students got is in finding inference ,with the mean score of 46.47 which is categorized into mediocre level. This result of this study suggest that the students to learn more about reading comprehension.Keywords : Study, Ability, Reading Comprehension.